De la monumentalisation à la théâtralité: Essai sur l’enceinte urbaine en Italie centrale du VIIIe au Iers. av. J.-C - Fontaine, Paul (Res antiquae, 2022)
This article aims the ancient fortifications, looking at their monumentalisation and theatricality, using these modern concepts for better understandig of ancient practices. The focus is put on the city-walls of Central Italy from the 8th to 1st centuries BC. Ancient and modern meanings of “monument” are confronted to introduce an up-dated discussion on the relationship between monumentalisation of the fortifications and urban development in Preroman context. The theatricality of the city-walls, a growing phenomenon from the 3th century, takes on different forms for which are presented exemples from Etruria and Umbria.